An Implicit Stereotype of the Rich and Its Relation to Psychological Connectedness. (19th July 2017) - Liu, Chang-Jiang; Zhang, Yue; Hao, Fang
This study investigates people's implicit stereotype of the social group of the rich in terms of competence and warmth. We further examine the stereotype's relationship with temporal selves. Implicit Association Tests were used as measures of implicit social perception in a social comparison context. We also rated the degree of psychological connectedness between current and possible future selves across time. Our results demonstrate that the rich are implicitly perceived as having high levels of competence and low levels of warmth compared to the average person, and that a close psychological connectedness mitigates the negative perception of the rich. The implications and limitations of these findings are also discussed.